Implementation of A Genre Pedagogy Approach Based on The Contextualization of Jambi Local Legends in Learning Narrative Writing - Supriadi, Supriadi (IKIP PGRI Bojonegoro, 2026)
This study aims to describe the implementation process and analyze the results of the application of the Genre Pedagogy (PG) Approach synergized with the contextualization of Jambi Local Legends in narrative writing learning. The research design used is an Intrinsic Qualitative Case Study located at MAN 5 Batang Hari. The research subjects included Indonesian Language teachers and grade X-1 students. Data were collected through classroom observations (to record the PG cycle), in-depth interviews (with teachers and students), and document analysis (students' narrative writing results). Key findings show that 85% of students' writing results successfully contain a generic scheme or complete basic narrative structure, supported by a significant increase in writing motivation (student interview data). The contextualization of Jambi Local Legends has been proven to shorten the time to understand the initial context and activate students' cognitive structures quickly. This study concludes that the local content-based PG approach is a valid and relevant strategy to improve narrative writing competency in Madrasah educational environments.